Katara liberation from gender stereotypes in Avatar The Last Airbender movie 2024: A feminist analysis - Helmitik, Helmitik; Muhid, Ahmad; Ayunda, Nenin Astiti (Universitas Aki, 2025)
Film is an effective tool for inserting teachings and propaganda. Films always influence and shape society through the messages they convey. This research is a feminist study of Katara's character and her liberation from gender stereotypes in the film Avatar the Last Airbender Season 1, 2024. This research aims to see how Katara's character challenges the traditional gender norms that have long been established in society, as well as to examine how Katara's character develops in the film to the point of how she breaks free from these gender stereotypes. This research uses a qualitative descriptive approach. The data consists of conversations containing issues of patriarchy and gender stereotypes. The data sources are videos/films and conversation scripts within the film. Data collection was done through observation by repeatedly watching the film and then analysing it. The results show that Katara's character challenges gender norms by applying characteristics such as overcoming fear and embracing self-expression, defying the need for a handsome hero, embracing personal power and autonomy, and empowering brotherhood over romantic love. This is followed by Katara's character development, which eventually frees her from gender stereotypes, gains recognition from society, and creates equality for herself and future generations